Differences in coordination and balance between male and female elite sport climbers - Stankovic, M.; Aras, D.; Rakovic, A. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
A very small number of authors studied coordination and balance as important motor skills responsible for success in sport climbing. Also, a small number of studies have been conducted on the differences between male and female sport climbers. The aim of this study was to determine the differences in coordination and balance between mele and female elite sport climbers. The research was conducted on 21 elite sport climbers (10 males aged 17.3±1.57 years and 11 females aged 16.0±1.55 years), Youth World Cup participants held in Arco, Italy. Study was carried out using six variables (three for the evaluation of the coordination and three for balance). The results indicate that globally there are no significant differences in coordination between male and female elite sport climbers, except in the coordination with a baton test in which men were statistically significantly more successful. However, there are statistically significant differences in balance at the multivariate level in favor of men, as well as in the Flamingo test, while the crosswise standing test on a balance bench was at the very limit of significance. These results probably point out at two more possible components in the specification equation that make male elite sport climbers still climb harder routes than female elite sport climbers.